Penegakan Hukum terhadap Tindak Pidana Perdagangan Orang di Polda NTB - Muhammad Hijratul Azmi; Ufran Ufran (UKInstitute, 2023)
This study aims to determine how to the criminal law enforcement act of human trafficking at the NTB Regional Police and to find out what are the obstacles in law enforcement the criminal act of trafficking in persons at the NTB Regional Police. The type of research used is empirical legal research methods, with statutory, conceptual, and sociological approaches. Based on this research, the investigation of human trafficking in the NTB Police is carried out in two stages, namely investigation and investigation. The investigation stage starts from receiving a Notification of the Return of Indonesian Citizens/PMI to receiving a case delegation letter from the National Police Headquarters, then the investigation starts from making an investigation warrant to making a notification of the progress of the investigation results (SP2HP). The internal obstacle experienced by the NTB Regional Police investigators is that the investigator cannot detain overseas agents who are involved in the criminal act of trafficking in persons because they do not know the agent's whereabouts. Meanwhile, external constraints can be seen from the legal factors themselves, law enforcement factors, supporting facilities or facilities, and community factors.